Influence of coding variability in APP-Aß metabolism genes in sporadic Alzheimer's disease - Sassi, C.; Ridge, P.; Nalls, M.A.; Gibbs, R.; Ding, J.; Lupton, M.K.; Troakes, C.; Lunnon, K.; Al-Sarraj, S.; Brown, K.S.; Medway, C.; Lord, J.; et al. (Public Library of Science, 2016)
The cerebral deposition of Aß42, a neurotoxic proteolitic derivate of amyloid precursor protein (APP), is a central event in Alzheimer’s disease (AD)(Amyloid hypothesis). Given the key role of APP-Aß metabolism in AD pathogenesis, we selected 29 genes involved in APP processing, Aß degradation and clearance. We then used exome and genome sequencing to investigate the single independent (single-variant association test) and cumulative (gene-based association test) effect of coding variants in these genes as potential susceptibility factors for AD, in a cohort composed of 435 sporadic and mainly late-onset AD cases and 801 elderly controls from North America and the UK. Our study shows that common coding variability in these genes does not play a major role for the disease development. In the single-variant association analysis, the main hits, which were nominally significant, were found to be very rare coding variants (MAF 0.3%-0.8%) that map to genes involved in APP processing (MEP1B), trafficking and recycling (SORL1), Aß extracellular degradation (ACE) and clearance (LRP1). Moreover, four genes (ECE1, LYZ, TTR and MME) have been found as nominally associated to AD using c-alpha and SKAT tests. We suggest that Aβ degradation and clearance, rather than Aβ production, may play a crucial role in the etiology of sporadic AD.